1994
DOI: 10.1021/jm00034a015
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Nonclassical Furo[2,3-d]pyrimidines as Novel Antifolates: Synthesis and Biological Activities

Abstract: Classical antifolate analogues containing a novel furo[2,3-d]pyrimidine ring system which include N-[4-[N-[(2,4-diaminofuro[2,3-d]pyrimidin-5- yl)methyl]amino]benzoyl]-L-glutamic acid (1) and its N-9 methyl analogue 2 were synthesized as potential dual inhibitors of thymidylate synthase (TS) and dihydrofolate reductase (DHFR) and as antitumor agents. Four nonclassical antifolates, 2,4-diamino-5-(anilinomethyl)furo[2,3-d]pyrimidines 3-6 with 3,4,5-trimethoxy, 3,4,5-trichloro, 3,4-dichloro, and 2,5-dimethoxy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 8 publications
3
93
1
Order By: Relevance
“…Gangjee et al reported [7][8][9][10] the synthesis of two-carbon atom bridged furo [2,3-d] which on hydrogenation would give the desired target compounds. However the Wittig reaction of I and (1-chloro-ethyl)-benzene under a variety of different conditions of time, base, temperature and solvent failed to afford the desired product III.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gangjee et al reported [7][8][9][10] the synthesis of two-carbon atom bridged furo [2,3-d] which on hydrogenation would give the desired target compounds. However the Wittig reaction of I and (1-chloro-ethyl)-benzene under a variety of different conditions of time, base, temperature and solvent failed to afford the desired product III.…”
Section: Resultsmentioning
confidence: 99%
“…Gangjee et al [5][6][7][8][9][10] reported two-atom bridged classical and non-classical, 6-5 bicyclic analogs, as potential DHFR inhibitors (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some 6-5 bicyclic pyrrolo[2, 3-d]pyrimidines such as compounds 3 and 4 TNP351 8,9 were also reported as potent antifolates. Gangjee et al [10][11][12] reported a series of novel furo[2,3-d]pyrimidines 5-9 as potent antifolates. A 2,4-diamino-substituted pyrimidine ring is considered important for potent DHFR inhibition, while a 2-substituted-4-oxopyrimidine ring is considered important for TS inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…A 2,4-diamino-substituted pyrimidine ring is considered important for potent DHFR inhibition, while a 2-substituted-4-oxopyrimidine ring is considered important for TS inhibition. 2,13,14 Gangjee et al 10,11 suggested a dual DHFR-TS inhibitor model and proposed two binding modes for the 2-amino-4-oxo-pyrrolo[2, 3-d]pyrimidine system as well as the 2,4-diamino-furo[2, 3-d]pyrimidine (Fig. 2), Gangjee et al 15 demonstrated that compound 10, a 4-methyl analog of compound 3, binds in the alternate mode to DHFR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation